2011
DOI: 10.5194/bg-8-2257-2011
|View full text |Cite
|
Sign up to set email alerts
|

Planktonic dinitrogen fixation along a longitudinal gradient across the Mediterranean Sea during the stratified period (BOUM cruise)

Abstract: Abstract. This study provides extensive data on planktonic N 2 fixation rates across the whole Mediterranean Sea. They show that N 2 fixation occurs in Mediterranean waters during the stratification period, with a clear decreasing trend from the oligotrophic western basin (10-76 µmol m −2 d −1 ) to the ultra oligotrophic eastern basin (0-0.4 µmol m −2 d −1 ). Highest rates are measured in the less oligotrophic western basin, between the surface and 75 m-depth, where 45 to 75 % of N 2 fixation are found within … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
73
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 59 publications
22
73
1
Order By: Relevance
“…Regarding the impact on nutrients fuxes, however, Bonnet et al (2011) have shown that the vertical nitrogen turbulent fuxes determined from K z values obtained in eddies still balance only a small fraction of the nitrogen fluxes resulting from primary production, suggesting a main contribution of regenerated production. Vertical advection was not considered in this study and may also provide significant vertical transport of nutrients, as suggested in previous studies (Ledwell, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the impact on nutrients fuxes, however, Bonnet et al (2011) have shown that the vertical nitrogen turbulent fuxes determined from K z values obtained in eddies still balance only a small fraction of the nitrogen fluxes resulting from primary production, suggesting a main contribution of regenerated production. Vertical advection was not considered in this study and may also provide significant vertical transport of nutrients, as suggested in previous studies (Ledwell, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A large part of the BOUM experiment was dedicated to the precise characterization of biogeochemical processes within three oligotrophic environments, namely anticyclonic eddies (eddies A, B, C) (Moutin and Prieur, 2012). During the experiment special effort was made to determine the physical forcing, and specifically the vertical mixing in these environments, which impacts most of biogeochemical processes studied and modeled within the BOUM project (Bonnet et al, 2011;Mauriac et al, 2011). Another point of interest is the impact of vertical turbulent mixing on the water masses evolution and water massed circulation in the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%
“…This K z value, with an estimated error of about 40 % ( Table 2 in Cuypers et al, 2012), was considered constant. N-input by N 2 fixation is the mean integrated value measured in the photic zone, and atmospheric deposition is a mean value taken in the absence of rain (Bonnet et al, 2011 and further references herein, Table 1). The estimated errors could be 30-40 % (Bonnet et al, 2011, their Table 1).…”
Section: Daily N-budget At the Ld Stationsmentioning
confidence: 99%
“…N-input by N 2 fixation is the mean integrated value measured in the photic zone, and atmospheric deposition is a mean value taken in the absence of rain (Bonnet et al, 2011 and further references herein, Table 1). The estimated errors could be 30-40 % (Bonnet et al, 2011, their Table 1). New N-input corresponds to the sum of these three N-fluxes, because other possible inputs T. Moutin and L. Prieur: Influence of anticyclonic eddies on BOUM 3833 Table 3.…”
Section: Daily N-budget At the Ld Stationsmentioning
confidence: 99%
See 1 more Smart Citation